Importance of Iron Complexation for Fenton-Mediated Hydroxyl Radical Production at Circumneutral pH - Miller, Christopher J.; Rose, Andrew L.; Waite, T. David (Frontiers in Marine Science, 2016)
The reaction between Fe(II) and H2O2 to yield hydroxyl radicals (HO•), the Fenton reaction, is of interest due to its role in trace metal and natural organic matter biogeochemistry, its utility in water treatment and its role in oxidative cell degradation and associated human disease. There is significant dispute over whether HO•, the most reactive of the so-called reactive oxygen species, is formed in this reaction, particularly under circumneutral conditions relevant to natural systems. In this work we have studied the oxidation kinetics of Fe(II) complexed by L = citrate, ethylenediaminetetraacetic acid (EDTA) and diethylenetriaminepentaacetic acid (DTPA) and also measured HO• production using phthalhydrazide as a probe compound at pH 8.2. It is shown that HO• is the sole product of the Fe(II)L-H2O2 reaction for L = EDTA and DTPA, with kinetic modelling of the full reaction pathway utilized to confirm this finding. Quantitative HO• production also appears likely for L = citrate, although uncertainties with the speciation of Fe(II)-citrate complexes as well as difficulties in modelling the oxidation kinetics of these complexes has prevented a definitive conclusion. In the absence of ligands at circumneutral pH, inorganic Fe(II) reacts with H2O2 to yield a species other than HO•, contrary to the well-established production of HO• from inorganic Fe(II) at low pH. Our results suggest that at high pH Fe(II) must be complexed for HO• production to occur.